PELATIHAN PETANI KELAPA DALAM MELAKUKAN PENGOLAHAN LIMBAH AIR KELAPA MENJADI KECAP MANIS GUNA PENINGKATAN EKONOMI MASYARAKAT DESA TOARI KABUPATEN KOLAKA - Fitrianti Handayani; Djurnarlin Tojang; Fitrah Adelina; Juniaty Arruan Bulawan; Qadaruddin Fajri Adi; Saparuddin; Mustafa R Mustafa; Abdul Rahim; Maretik Maretik; Erfina Erfina (Universitas Mataram, 2023)
Toari Village is the largest coconut producing village in Kolaka Regency. The people only process coconuts as copra while the water becomes waste, causing problems because of its strong aroma after being thrown away. Therefore, it is very important to provide training to the Toari Village Community in processing coconut water waste. One of the products produced is sweet soy sauce. Sweet soy sauce is a type of food additive that is popular because it makes the food taste better. The aim of this service is to create community independence in processing coconut water into products of high economic value and to gain skills in processing coconut water so that it can be used by the community to improve the economy. This service method is carried out at several stages including the observation stage, preparation stage, activity implementation stage, training and mentoring stage, and evaluation stage. The result of this activity is that the community is very enthusiastic about participating in the training so that the sweet soy sauce products produced are very good, taste good and are hygienic. The level of community skills and knowledge after carrying out training and mentoring activities has increased by 100% and several service outcomes have been achieved.